You can rewrite the given equation \( 4x^3 - 12 + 3 = 10 \) as two equations joined by "and" as follows:
\( 4x^3 - 12 + 3 = 10 \) and \( 4x^3 - 12 + 3 - 10 = 0 \).
This simplifies to:
\( 4x^3 - 9 = 10 \) and \( 4x^3 - 9 = 0 \).
in two equations joined by “and.”
11 answers
You can rewrite the given equation \( 4x^3 - 12 + 3 = 10 \) as two equations joined by "and" as follows:
\( 4x^3 - 12 + 3 = 10 \) and \( 4x^3 - 12 + 3 - 10 = 0 \).
This simplifies to:
\( 4x^3 - 9 = 10 \) and \( 4x^3 - 9 = 0 \).
Certainly! Let's break down the process of rewriting the equation \( 4x^3 - 12 + 3 = 10 \) into two equations joined by "and" step by step.
The original equation is: \[ 4x^3 - 12 + 3 = 10 \]
First, simplify the left side of the equation:
Now, we can rearrange this equation to isolate one side: \[ 4x^3 - 9 - 10 = 0 \] This simplifies to: \[ 4x^3 - 19 = 0 \]
We now have two forms:
We can now write these as two equations joined by "and": \[ 4x^3 - 9 = 10 \quad \text{and} \quad 4x^3 - 19 = 0 \]
Thus, the original equation can be expressed as: \[ 4x^3 - 9 = 10 \quad \text{and} \quad 4x^3 - 19 = 0 \]
This concludes the step-by-step process!
Of course! Here's a simplified step-by-step breakdown of rewriting the equation \( 4x^3 - 12 + 3 = 10 \) into two equations joined by "and."
The original equation is: \[ 4x^3 - 12 + 3 = 10 \]
Combine the constants on the left side: \[ -12 + 3 = -9 \] So, we rewrite the equation as: \[ 4x^3 - 9 = 10 \]
Now, we manipulate the equation to set one side to zero: \[ 4x^3 - 9 - 10 = 0 \] This simplifies to: \[ 4x^3 - 19 = 0 \]
Now we can write the two equations:
We can now express these as: \[ 4x^3 - 9 = 10 \quad \text{and} \quad 4x^3 - 19 = 0 \]
The final answer is: \[ 4x^3 - 9 = 10 \quad \text{and} \quad 4x^3 - 19 = 0 \]
This completes the process!
Thank you so much for your kind words! I'm glad to hear that you found my assistance helpful. If you have any more questions or need further assistance, feel free to ask. I'm here to help!
Sure! Let's solve the equation \( 3.5 \cdot 1.2^x = 5.4 \) for the variable \( x \) step by step.
We start with the equation: \[ 3.5 \cdot 1.2^x = 5.4 \] To isolate \( 1.2^x \), divide both sides of the equation by \( 3.5 \): \[ 1.2^x = \frac{5.4}{3.5} \]
Now, calculate \( \frac{5.4}{3.5} \): \[ \frac{5.4}{3.5} \approx 1.542857 \] So we have: \[ 1.2^x \approx 1.542857 \]
To solve for \( x \), take the logarithm (we can use natural logarithm \( \ln \) or common logarithm \( \log \)). Here we will use natural logarithm: \[ \ln(1.2^x) = \ln(1.542857) \]
By applying the power rule of logarithms \( \ln(a^b) = b \cdot \ln(a) \), we get: \[ x \cdot \ln(1.2) = \ln(1.542857) \]
Now, divide both sides by \( \ln(1.2) \) to solve for \( x \): \[ x = \frac{\ln(1.542857)}{\ln(1.2)} \]
Now, use a calculator to find the values of the logarithms:
Substituting these values into the equation: \[ x \approx \frac{0.4343}{0.1823} \approx 2.384 \]
Thus, the solution for \( x \) is approximately: \[ x \approx 2.384 \]
If you need further assistance or clarification, feel free to ask!
Absolutely! Here’s a simplified and more straightforward approach to solving the equation \( 3.5 \cdot 1.2^x = 5.4 \):
Using these values: \[ x \approx \frac{0.187}{0.079} \approx 2.37 \quad (\text{approximately}) \]
Thus, the solution is: \[ x \approx 2.37 \]
This version condenses the steps while providing a clear direction for solving the equation! If you have any further questions, feel free to ask.